2018
DOI: 10.1007/s00592-018-1196-x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of effective transition from pediatric to adult diabetes care: epidemiological and clinical characteristics—a pioneering experience in North Africa

Abstract: This program was beneficial for 75% of patients who demonstrated an improvement in their metabolic control the year following transition to adult care service. To our knowledge, this study is the first one in North Africa to report on the outcome of a structured transition program from pediatric to adult diabetes care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…But none of our included studies examined the flexibility of transfer time as a sole intervention. In most studies, the timing was linked to individual HCT planning [24,30,31]. In other studies, the time of transfer was determined by an HCT coordinator [32].…”
Section: The Time Of Transfer Should Take Into Account the Characteristics Of The Disease And The Patient And Should Not Be Rigidly Linkementioning
confidence: 99%
“…But none of our included studies examined the flexibility of transfer time as a sole intervention. In most studies, the timing was linked to individual HCT planning [24,30,31]. In other studies, the time of transfer was determined by an HCT coordinator [32].…”
Section: The Time Of Transfer Should Take Into Account the Characteristics Of The Disease And The Patient And Should Not Be Rigidly Linkementioning
confidence: 99%
“…But none of our included studies examined the exibility of transfer time as a sole intervention. In most studies, the timing was linked to individual transition planning [24,30,31]. In other studies, the time of transfer was determined by a transition coordinator [32].…”
Section: Level Of Recommendationmentioning
confidence: 99%
“…Cole and co-workers observed better drug adherence, greater use of the rst appointment, fewer operations, and fewer hospital admissions in the rst two years after transfer in young patients with in ammatory bowel disease [30]. In young people with type 1 diabetes the HbA1c value improved signi cantly [31]. Jensen and colleagues showed a higher rate of successful HCT in adolescents with juvenile idiopathic arthritis after complex care coordinated by a social worker [32].…”
Section: Level Of Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review by Schmidt et al (35) showed that the structured, professionally guided HCT process (planning, transfer assistance, and integration) resulted in improvements in disease-specific measures, quality of life, and self-care skills. Several studies demonstrated an improvement in the glycemic control of young T1DM patients following a structured transition program from pediatric to adult diabetes care (36)(37)(38)(39); however, the prevalence of neuropathic lesions in young patients with T1DM at the time of transition is not known. Our goal was to assess the possible neuropathic condition of this special population at the time of transition to define the potential earlier screening needs.…”
Section: Introductionmentioning
confidence: 99%